Modern Incidence of Complete Heart Block in Patients with L‐looped Ventricles: Does Univentricular Status Matter?. (15th June 2015) - Simmons, M. Abigail; Rollinson, Nancy; Fishberger, Steven; Qin, Li; Fahey, John; Elder, Robert W.
Abstract Objective Individuals with L‐transposition of the great arteries and two normally sized ventricles are at risk for complete heart block. Little is known about the incidence of complete heart block in those with a single ventricle L‐transposition of the great arteries. In this study, we compare the incidence of complete heart block in a modern cohort of patients with L‐looped single ventricle anatomy to patients with L‐transposition of the great arteries and two ventricles. Methods We conducted a retrospective cohort study of patients with L‐transposition of the great arteries who were seen at Yale‐New Haven Hospital between 2001 and 2013. Patients were classified as having isolated L‐transposition of the great arteries (group I), L‐transposition of the great arteries and major cardiac defects with two‐ventricle anatomy (group II), or L‐transposition of the great arteries and single ventricle anatomy (group III). We recorded the age of onset and the circumstances of CHB in each group. We calculated the incidence rate of complete heart block and compared this between the groups. Results We identified 64 patients with L‐transposition of the great arteries, median age of 21 years (range 6 months–52 years): 21 in group I, 15 in group II, and 28 in group III. In total, 15 subjects developed complete heart block, incidence of 21.9% and rate of 1.3% per person years. Although group III patients were significantly less likely to develop complete heart block than dual ventricle patients (7.1% vs. 33% and 40%, P = .01), this difference is not significant when only spontaneous complete heart block was analyzed (P = .16). Conclusion All patients with L‐transposition of the great arteries have similar risk of spontaneous complete heart block and should be routinely screened for this complication.